CSR and firm survival: Evidence from the climate and pandemic crises - Thomas J. Chemmanur; Dimitrios Gounopoulos; Panagiotis Koutroumpis; Yu Zhang (Queen Mary University of London, School of Economics and Finance, 2022)
We analyse the relationship between the extent of a firm's corporate social responsibility (CSR) and its long-term survival probability. We conjecture that a better CSR rating is associated with a lower probability of corporate failure and a longer survival period. Consistent with this, we document that four CSR dimensions (environment, community, employee relations, and product) out of six are positively related to firms' survival probability. The positive association between CSR ratings and firm survival is stronger for firms operating in more competitive industries and those with weaker governance. We find that a firm's engagement in CSR activities is particularly crucial for firm survival during pandemics and under adverse climate conditions. We establish causality in the relation between a firm's CSR activities and its survival probability using instrumental variable (IV) and Heckman twostep analyses. Finally, we find that better financial performance, less stringent financial constraints, greater managerial discipline, and enhanced labor productivity are some of the channels through which firms engaging in more CSR activity achieve longer survival times.
Keywords: G30; G41; M14; 330; Corporate Social Responsibility; Climate Change; Pandemic Uncertainty; Firm Survival; Corporate Governance